THE DEFENSE MECHANISM OF IAGO AS A TRAITOR TO BUILD TRUST IN OTHELLO WILLIAM SHAKESPEARE DRAMA: A PSYCHOANALYTIC APPROACH - Bani, Yoga N (2011)
This research is aimed to analyze the structural elements of the August Rush in August Rush movie by Kristen Sheridan such as character and characterization, plot, point of view, style and theme based on individual psychological perspective. This research is a qualitative research. The data are taken from document analysis. The object of the study is the anxiety in finding self identity of august rush in august rush movie. The result of study show a close relationship between August Rush movie and Psychoanalytic, particularly in conscious and unconscious or the id, ego and superego of Evan in finding his identity through music. In August Rush movie, Evan the most have his realistic anxiety, like the explanation above that Evan is a kid who has a natural nature that isn‟t change with the surround. Evan start when he knows that he needs her parent to grows him up. Every day and every night before or while sleep, Evan always think and dreams that his parent still alive somewhere. Behind his blanket he always smiles and plants his confidence within. That is natural for a kid. While the other anxiety (neurotic and moral anxiety) it‟s only support the realistic anxiety as a basic nature of human when they‟re kid. It can be explain that in this Evan‟s Id is the most dominant then superego and ego is the most dominant then superego. It can be seen that because Evan‟s id and ego is a natural nature of kids that isn‟t changed at all with the surround neighborhood. Evan finally chooses to run from Wizard in favor of performing at his concert. In the meantime, Louis races to the park when he sees Evan's pseudonym along with Lyla's name on a sign billing the concert. Evan conducts his piece, and at its conclusion, when he turns around to see Lyla and Louis standing hand in hand, he knows that he is reunited with his mother and father at last